Development of a Community-Based Intervention Model through Infused Water Consumption for Blood Pressure Control in Hypertensive Patients - Lisnawati, Ica; Anwari, Muhammad; Munadi, M. Hasni; Panda, M. Imannuddin; hair, Abdul; Prananda, Yuda; Ratnatina, Ratnatina; Ermayanty, Wafa; Ra’fah, Siti; Faujiah, Utami (UrbanGreen Central Media, 2024)
Hypertension is a non-communicable disease that is commonly suffered by the people in Hulu Sungai Utara Regency. Based on a windshield survey conducted in RT.2 of Kalumpang Luar Village, it was found that around 39.6% of the population suffers from hypertension. This disease is often referred to as a